Controlling for Risk: An Analysis of China’s System of Foreign Exchange and Exchange Rate Management - Hall, Thomas (Columbia Journal of Asian Law, 2004)
After more than twenty years of rapid development of China’s economy and foreign trade sector, both China itself and the rest of the world are for the first time coming to grips with the reality that China’s economic policy choices now have global repercussions. As the international consciousness of China’s influence grows, China’s economic policies have naturally come under increasing criticism from countries that feel they are being affected negatively by those policies. This phenomenon can be seen in the recent controversy surrounding China’s foreign exchange regime and pegged exchange rate system. Calls on China to revalue or float its currency – coming primarily from Japan and the United States – have been intensifying since late 2002.’ The accumulating international political pressure for China to adjust its exchange rate policy has sparked intense debate among economic and political analysts concerning the appropriate foreign exchange and exchange rate system for China. While this debate has focused principally on China’s choice of exchange rate mechanism, i.e. the pros and cons of letting the RMB float according to market demand and supply versus pegging the currency to one degree or another, the debate has also encompassed China’s overall policy of maintaining restrictions on the free flow of foreign currency and the convertibility of the RMB.